Whisper‐like behavior in a non‐human primate. Issue 6 (13th September 2013) - Morrison, Rachel; Reiss, Diana
<x xml:space="preserve">Abstract</x> In humans, whispering has evolved as a counteractive strategy against eavesdropping. Some evidence for whisper‐like behavior exists in a few other species, but has not been reported in non‐human primates. We discovered the first evidence of whisper‐like behavior in a non‐human primate, the cotton‐top tamarin (Saguinus oedipus), in the course of investigating their use of human‐directed mobbing calls. We exposed a family of captive cotton‐top tamarins to a supervisor who previously elicited a strong mobbing response. Simultaneous audio–video recordings documented the animals' behavioral and vocal responses in the supervisor's presence and absence. Rather than exhibiting a mobbing response and producing loud human‐directed mobbing calls, the tamarins exhibited other anti‐predator behaviors and produced low amplitude vocalizations that initially eluded our detection. A post‐hoc analysis of the data was conducted to test a new hypothesis—the tamarins were reducing the amplitude of their vocalizations in the context of exposure to a potential threat. Consistent with whisper‐like behavior, the amplitude of the tamarins' vocalizations was significantly reduced only in the presence of the supervisor. Due to its subtle properties, this phenomenon may have eluded detection in this species. Increasing evidence of whisper‐like behavior in non‐human species suggests that such low amplitude signaling may represent a convergence in a communication strategy amongst highly social and cooperative species. Zoo Biol. 32:626–631, 2013. © 2013 Wiley Periodicals, Inc.